A reliable and time‐saving semiautomatic spike‐template–based analysis of interictal EEG–fMRI. Issue 12 (6th November 2014) - Tousseyn, Simon; Dupont, Patrick; Robben, David; Goffin, Karolien; Sunaert, Stefan; Van Paesschen, Wim
Summary Objective A prerequisite for the implementation of interictal electroencephalography–correlated functional magnetic resonance imaging (EEG‐fMRI) in the presurgical work‐up for epilepsy surgery is straightforward processing. We propose a new semi‐automatic method as alternative for the challenging and time‐consuming visual spike identification. Methods Our method starts from a patient‐specific spike‐template, built by averaging spikes recorded on the EEG outside the scanner. Spatiotemporal cross‐correlations between the template and the EEG measured during fMRI were calculated. To minimize false‐positive detections, this time course of cross‐correlations was binarized by means of a spike‐template–specific threshold determined in healthy controls. To inform our model for statistical parametric mapping, this binarized regressor was convolved with the canonical hemodynamic response function. We validated our "template‐based" method in 21 adult patients with refractory focal epilepsy with a well‐defined epileptogenic zone and interictal spikes during EEG‐fMRI. Sensitivity and specificity for detecting the epileptogenic zone were calculated and represented in receiver operating characteristic (ROC) curves. Our approach was compared with a previously proposed semiautomatic "topography‐based" method that used the topographic amplitude distribution of spikes as a starting point for correlation‐based fitting. Results Good diagnostic performance could be reached with our template‐based method. The optimal area under the ROC curve was 0.77. Diagnostic performance of the topography‐based method was overall low. Significance Our new template‐based method is more standardized and time‐saving than visual spike identification on intra‐scanner EEG recordings, and preserves good diagnostic performance for detecting the epileptogenic zone.